Two-Stage Model of Silicate Glass Transition (Global Journal of Science Frontier Research, 2022)
After several decades of study, the nature of the glass state and glass transition remains controversial. This work describes a newly proposed two-stage model for silicate glass transition. The model recognizes that there is a cooling rate independent critical temperature Tc, separating two temperature regions. The coherent structures in the two regions change along different paths. All observed dynamic features in the glass transition result from structural rearrangements in the process. According to the proposed model, the silicate glass transition can be recognized as a second-order phase transition following an incomplete first-order phase transition. This work will first describe the two-stage model, and then apply the model to silica glass, as well as binary and ternary silicate glass transitions.
Keywords: silicate glasses; medium range ordering structure; glass transition; phase diagram; critical temperature